Technological Interventions in English Pedagogy: A Comprehensive Analysis of their Influence on Teaching and Learning of the English Language - Ningrum Tri Mulya; NHPS Putro (STAI Hubbulwathan Duri, 2024)
Technology literacy has become increasingly important in the context of teaching and learning English, especially with ongoing technological advancements. This study aims to examine the impact of technology on English education by analyzing recent literature on the subject. A systematic literature review was conducted using the Scopus database to collect relevant research on technology's role in English teaching and learning. The search initially identified 257 documents, narrowed down to 20 based on publication year and relevance to the topic, ensuring a focus on high-quality sources. Analysis of the selected studies revealed that technology significantly enhances the efficiency of English teaching and learning. Key findings indicate that technology facilitates greater access to educational resources, while multimedia tools and digital platforms offer interactive and engaging ways to support language acquisition. Furthermore, teachers’ proficiency with these tools is shown to correlate positively with student learning outcomes. The findings underscore the importance of technology literacy among English educators, as their skill in using technological media directly impacts students' learning results. Enhanced access to resources and multimedia-supported instruction not only enriches the educational experience but also aligns with modern learning preferences, suggesting a need for continued integration of technology in English education. This review highlights that technology in English teaching promotes resource accessibility and student engagement, ultimately improving learning outcomes. Continued development of teachers' technological skills is recommended to fully realize these benefits.